New Photometry and Spectra of AB Doradus C: An Accurate Mass Determination of a Young Low-Mass Object with Theoretical Evolutionary Tracks - Close, L; Thatte, N; Nielsen, E; Abuter, R; Clarke, F; Tecza, M (Institute of Physics Publishing, 2007)
We present new photometric and spectroscopic measurements for the unique, young, low-mass evolutionary track calibrator AB Dor C. While the new Ks photometry is similar to that previously published in Close et al. (2005) the spectral type is found to be earlier. Based on new H and K IFS spectra of AB Dor C (Thatte et al. 2007; paper 1) we adopt a spectral type of M5.5+/-1.0 for AB Dor C. This is considerably earlier than the M8+/-1 estimated in Close et al. (2005) and Nielsen et al. (2005) yet is consistent with the M6+/-1 independently derived by Luhman and Potter (2005). However, the spectrum presented in paper 1 and analyzed here is a significant improvement over any previous spectrum of AB Dor C. We also present new astrometry for the system which further supports a 0.090+/-0.005 Msun mass for the system. Once armed with an accurate spectrum and Ks flux we find L=0.0021+/-0.0005 Lsun and Teff=2925{+170}{-145}K for AB Dor C. These values are consistent with a ~75 Myr 0.090+/-0.005 Msun object like AB Dor C according to the DUSTY evolutionary tracks (Chabrier et al. 2000). Hence masses can be estimated from the HR diagram with the DUSTY tracks for young low-mass objects like AB Dor C. However, we cautiously note that underestimates of the mass from the tracks can occur if one lacks a proper (continuum preserved) spectra or is relying on NIR fluxes alone.